Genetic divergence of Anthurium affine germplasm using morphoagronomic and molecular descriptors (Revista Ciência Agronômica, 2020)
Anthurium affine is an ornamental Brazilian native plant very appreciated due to its long-lasting durability. Toexplore the genetic diversity available, 21 A. affine half-sibling progeny were evaluated using morphoagronomic and moleculardescriptors. The morphoagronomic descriptors used were: plant height, plant diameter, growth habit, leaf number, leaf bladelength, leaf blade width, petiole length, petiole diameter, leaf margin undulation, general appearance; soil cover rate and RandomAmplified Polymorphic DNA (RAPD) markers the molecular one. All the descriptors within the progeny showed variabilityand general appearance, leaf margin undulation and soil cover rate are the ones that most contribute to the plants divergence.From 45 RAPD primers tested, 19 presented clear polymorphic bands (42.2%). Those generated 200 molecular markers, 81(40.5%) of them being polymorphic. The number of polymorphic bands per RAPD primer ranged from one (OPB10) to eight(OPW11) and polymorphism ranged from 16.6% (OPB10) to 70% (OPW05). Grouping analysis of morphoagronomic andmolecular descriptors formed five and four groups respectively. The dendrograms showed differentiation between accessionsalthough there was no association between morphoagronomic and molecular groupings. There is genetic divergence within thehalf-sibling progeny of A. affine plants evaluated, which opens up possibilities for increase variability.